Palladium-Catalysed Reductive Aminocarbonylation of Aryl Bromides and Iodides with Nitroarenes - Blessing D. Mkhonazi; Euphrent M. Mabila; Paseka T. Moshapo (SynOpen, 2022)
Amide functional groups are a structural feature in a vast array of beneficial organic molecules. This has resulted in a surge in new methodologies developed to enable access to this functional group using a broad range of coupling partners. Herein, we report a palladium-catalysed reductive aminocarbonylation of aryl bromides and iodides with nitroarenes to afford the respective amide products. The developed protocol employs Mo(CO)6 as a carbonyl source and a combination of Zn and TMSCl as co-reducing agents. For most substrates, the anticipated amide products were obtained in modest to high amide product yields.